2015
DOI: 10.1002/jnr.23601
|View full text |Cite
|
Sign up to set email alerts
|

Altered superficial amygdala–cortical functional link in resting state after 36 hours of total sleep deprivation

Abstract: The superficial amygdala (SFA) is important in human emotion/affective processing via its strong connection with other limbic and cerebral cortex for receptive and expressive emotion processing. Few studies have investigated the functional connectivity changes of the SFA under extreme conditions, such as prolonged sleep loss, although the SFA showed a distinct functional connectivity pattern throughout the brain. In this study, resting-state functional magnetic resonance imaging (rs-fMRI) was employed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Time courses were compared within each run using the DPARSFA toolbox and the resulting z-statistics were entered into a mixed-effects linear regression model with deviation coding for contrasts in R 66 . In addition, following Shao et al 12 , we defined a thalamus region of interest (ROI) using the Wake Forest University PickAtlas 67-69 , and following Shao et al 12,13 and Lei et al 14 , we selected right and left thalamus ROI:s as well as separate ROI:s for the superficial, centromedial, and basolateral amygdala, as defined by Amunts et al 70 , using the Jülich atlas [71][72][73] . Furthermore, at the suggestion of one reviewer, we investigated default mode network using seed-based methods.…”
Section: Seed-based and Cross-correlation Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Time courses were compared within each run using the DPARSFA toolbox and the resulting z-statistics were entered into a mixed-effects linear regression model with deviation coding for contrasts in R 66 . In addition, following Shao et al 12 , we defined a thalamus region of interest (ROI) using the Wake Forest University PickAtlas 67-69 , and following Shao et al 12,13 and Lei et al 14 , we selected right and left thalamus ROI:s as well as separate ROI:s for the superficial, centromedial, and basolateral amygdala, as defined by Amunts et al 70 , using the Jülich atlas [71][72][73] . Furthermore, at the suggestion of one reviewer, we investigated default mode network using seed-based methods.…”
Section: Seed-based and Cross-correlation Analysesmentioning
confidence: 99%
“…Based on reports of effects of sleep deprivation on connectivity from the thalamus 12,22 and amygdala 13,14 , we investigated whether earlier results could be replicated. Seed regions are shown in supplemental figures 3 and 4 for thalamus and amygdala, respectively.…”
Section: Seed-based Analyses Of Connectivity With Thalamus and Amygdamentioning
confidence: 99%
See 1 more Smart Citation
“…A consistent and robust finding is that sleep deprivation caused reduced connectivity within the default mode network and reduced anticorrelation to the task-positive network 8 , 10 , 22 . Other findings include increased regional homogeneity (ReHo) in different brain areas following sleep deprivation 9 , 18 , changes in connectivity between the thalamus 12 and amygdala 13 , 14 and cortical areas. We formulated a number of hypotheses to try to replicate and extend these findings (see below).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several neuroimaging studies have now shown that SD results in hyper activation of the amygdala typically coupled with reduced amygdala‐prefrontal connectivity (see review by Goldstein and Walker []). Interestingly, resting‐state studies have also revealed significant alterations in the connectivity profile of the amygdala following 36 h of SD, reflecting preexisting changes in limbic network connectivity, prior to any task performance [Lei et al, ; Shao et al, ]. Changes in resting thalamic connectivity were also detected following SD, demonstrating a reduction in thalamic connectivity with multiple temporal and prefrontal regions [Shao et al, ], thought to reflect substantial changes in vigilance without sleep.…”
Section: Introductionmentioning
confidence: 99%